2021
DOI: 10.1111/jch.14171
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of weekly and biweekly intravenous CERA administration on erythropoiesis: A randomized controlled trial

Abstract: Although continuous erythropoietin receptor activators (CERAs) are widely used erythropoiesis‐stimulating agents for correcting renal anemia in patients undergoing hemodialysis (HD), few reports have examined weekly CERA administration. In this randomized controlled trial, we compared the efficacy and changes in the parameters of iron metabolism and erythropoiesis between weekly and biweekly CERA administration. In total, 120 patients undergoing maintenance HD were randomized to the weekly or biweekly group. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…These results are in line with the previously published studies, which have suggested a target Hb level of >10 g/dl in this patient population. 16,17,22 In this study, approximately half (51.46%) of the patients achieved Hb levels >10 g/dl at 3 months in both weekly and 10-day dose groups.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…These results are in line with the previously published studies, which have suggested a target Hb level of >10 g/dl in this patient population. 16,17,22 In this study, approximately half (51.46%) of the patients achieved Hb levels >10 g/dl at 3 months in both weekly and 10-day dose groups.…”
Section: Discussionmentioning
confidence: 58%
“…27 Recently, Kawai of anaemia was similar in weekly or biweekly CERA administration groups. 17 In line with these reports, the dosing used in our patients included a weekly dose or once every 10 days.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations